EML-Based Vector Radio-Frequency Optical Signal Generation Adopting Frequency Doubling With Precoding - Haichao Guo; Chaoyi Qin (IEEE Photonics Journal)
In this paper, an electroabsorption modulated laser (EML)-based vector radio-frequency (RF) optical signal generation scheme adopting frequency doubling and precoding is proposed and experimentally investigated. Compared with the expensive, large-size phase modulator, and intensity modulator, the EML is quite cost-efficient and much easier to integrate. Compared with the directly modulated laser, the EML has a larger bandwidth, which provides the possibility to generate huge bandwidth vector RF optical signal. We experimentally demonstrate the 4-GBd quadrature phase shift keying (QPSK) and 2-GBd 16-ary quadrature amplitude modulation (16 QAM) vector RF optical signal generation at 20 GHz, respectively. At the back-to-back case, the bit error rate (BER) can achieve the threshold of hard-decision feedforward error correction (HD-FEC) at 3.8 × 10−3. Moreover, 20-km single mode fiber-28 transmission causes no power penalty for the 20-GHz QPSK vector RF signal. To the best of our knowledge, this is the first time frequency doubling and precoding-based photonic vector RF signal generation adopting an EML has been demonstrated.